2021
DOI: 10.1109/access.2021.3108447
|View full text |Cite
|
Sign up to set email alerts
|

Early Recognition and Discrimination of COVID-19 Severity Using Slime Mould Support Vector Machine for Medical Decision-Making

Abstract: has spread rapidly across the world, leading to the insufficiency of medical resources in many regions. Early detection and identification of high-risk COVID-19 patients will contribute to early intervention and optimize medical resource allocation. Using the clinical data from the Affiliated Yueqing Hospital of Wenzhou Medical University (Yueqing, China), an evolutionary support vector machine model is designed to recognize and discriminate the severity of the COVID-19 by patients basic information and hemato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 185 publications
0
5
0
Order By: Relevance
“…The result shows that the spatial distribution of the efficiency of medical and health resource allocation in China is not random and some provinces tend to converge in the geographical space. Thus, Chinese health departments (36) should reasonably adjust the allocation of high-quality medical resources and focus on solving problems of redundancy or insufficiency of medical resource allocation (37) in provinces. The efficiency of resource allocation needs to be improved in order to match the demand for high-quality medical service.…”
Section: Discussionmentioning
confidence: 99%
“…The result shows that the spatial distribution of the efficiency of medical and health resource allocation in China is not random and some provinces tend to converge in the geographical space. Thus, Chinese health departments (36) should reasonably adjust the allocation of high-quality medical resources and focus on solving problems of redundancy or insufficiency of medical resource allocation (37) in provinces. The efficiency of resource allocation needs to be improved in order to match the demand for high-quality medical service.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that many patients remain concerned about the security of their medical information and may lack confidence in the ability of current technology to protect their privacy ( 41 ). Efficient and secure storage of data will be the next challenge; the processes of using this data should also comply with the informed consent of the owner, and data should be desensitized for use in order to avoid social problems such as discrimination ( 42 ). The advancement of these processes will also involve high economic costs and problems related to the improvement of relevant laws and regulations, which need to be addressed in the context of medical science.…”
Section: Discussionmentioning
confidence: 99%
“…They have been used to examine the show of classification models, including DL techniques. Hybrid operational strategy called the Enhanced Slim Mold Algorithm (ESMA) can unambiguously detect parameter optimization and feature selection for white holes, black holes, and wormholes in SVMs simultaneously [12]. The ESMA-SVM framework helps to reduce the chances of stagnation in the classification process and obtain high-quality classification results [13].…”
Section: Literature Surveymentioning
confidence: 99%